Studi Kelayakan Bisnis Pada Pengembangan Usaha King MuayThai Camp Bandung - Susilawati Susilawati; Taufik Purnama Hidayat; Anisa Rahman; Rama Anugrah; Tisa Yulisti Suherliatisyah (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Muay Thai is a martial art originating from Thailand called "The Art of Eight Limbs". This research examines whether the development of the King Muay Thai business is feasible from a marketing perspective, whether the development of the King Muay Thai business is feasible from a technical and operational perspective, whether the development of the King Muay Thai business is technically feasible and operationally feasible. feasible from an organizational and management point of view, if the commercial development of King Muay Thai is feasible from a financial point of view. The aim to be achieved in this research is to produce a commercially viable plan through implementation aspects, from the marketing strategy aspect used by King Muaythai Camp, the implementation of operational technical aspects carried out at King Muaythai Camp, organizational structure management. aspects of survival at King Muaythai Camp and business feasibility with a focus on financial aspects at King Muaythai Camp Bandung. This research uses a quantitative method where we conducted direct interviews with the owner of King Muaythai Camp to obtain information on marketing aspects, technical and operational aspects, organizational and management aspects, and financial aspects at King Muaythai Camp.